2022
DOI: 10.1016/j.ebiom.2022.103813
|View full text |Cite
|
Sign up to set email alerts
|

Generating 3D human cardiac constructs from pluripotent stem cells

Abstract: Human pluripotent stem cell (hPSC) technology has offered nearly infinite opportunities to model all kinds of human diseases in vitro. Cardiomyocytes derived from hPSCs have proved to be efficient tools for cardiac disease modeling, drug screening and pathological mechanism studies. In this review, we discuss the advantages and limitations of 2D hPSC-cardiomyocyte (hPSC-CM) system, and introduce the recent development of three-dimensional (3D) culture platforms derived from hPSCs. Although the development of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(59 citation statements)
references
References 109 publications
(148 reference statements)
1
58
0
Order By: Relevance
“…Gene expression changes, protein abundance and mitochondrial effects, though beyond the scope of this study are warranted to better understand differences in neuronal subtypes and their downstream signaling mechanisms post CCM stimulation. Some other general limitations of in vitro iPSC models are discussed elsewhere in detail (Feaster et al, 2021 ; Liu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression changes, protein abundance and mitochondrial effects, though beyond the scope of this study are warranted to better understand differences in neuronal subtypes and their downstream signaling mechanisms post CCM stimulation. Some other general limitations of in vitro iPSC models are discussed elsewhere in detail (Feaster et al, 2021 ; Liu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…150,151 These cells can be transdifferentiated into cardiomyocytes (called hPSC-derived cardiomyocytes, hPSC-CMs) for analysis (Figure 7A). 152,153 It has been found that multicellular cardiac microtissues induced by hiPSCs in vitro could be used to model arrhythmias and other cardiac diseases. 154,155 By simulating the external environment of the cells through microfluidic systems, those low-cost and high-throughput iPSCderived cardiac models have shown great advantages in disease modeling.…”
Section: Ooc Technology For Cardiac Regenerationmentioning
confidence: 99%
“…It has been used as a basic principle for spheroid generation, such as hanging drops, low-binding surfaces, and spinner flasks. [21][22][23] Endogenous components of the ECM, such as fibronectin, are, along with integrins, the main recognition molecules for cell adhesion. [24] Fibronectin is usually glycosylated and contains a cell adhesion sequence (arginine-glycine-aspartic acid [RGD]), which can promote cell-substratum detachment and cell-cell adhesion by binding to integrins.…”
Section: Introductionmentioning
confidence: 99%